Synthesis of New Chiral Diaryliodonium Salts - Brown, Michael; Delorme, Marion; Malmedy, Florence; Malmgren, Joel; Olofsson, Berit; Wirth, Thomas (Synlett, 2015)
A structurally diverse range of chiral diaryliodonium salts have been synthesised which have potential application in metal-free stereoselective arylation reactions.
Keywords: arylation; diaryliodonium salts; hypervalent iodine; stereoselective synthesis